Map no. 1 from the western boundary of Missouri to the mouth of Trap Creek from explorations and surveys [cartographic material] - Gunnison, J. W. (John Williams), 1812-1853; Beckwith, E. G. (Edward Griffin), 1818-1881; Kern, Richard H., 1821-1853; Egloffstein, F. W., 1824-1885; Siebert, Selmar (Engraved by Selmar Siebert, 1855)
Photocopy of a surveyor's map of western Missouri and eastern Kansas from the 1853 military expedition to survey a potential Pacific railroad line, showing drainage, existing rail lines, and towns. Includes territory as far south as the White River/Forsyth, Mo.; as far north as the Skunk River/Burlington, Iowa; as far east as Washington, Mo.; and as far west as Tecumseh, Kansas.